2015
DOI: 10.1103/physreve.91.022710
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth of wrinkled biofilms

Abstract: Biofilms are antibiotic-resistant bacterial aggregates that grow on moist surfaces and can trigger hospitalacquired infections. They provide a classical example in biology where the dynamics of cellular communities may be observed and studied. Gene expression regulates cell division and differentiation, which affect the biofilm architecture. Mechanical and chemical processes shape the resulting structure. We gain insight into the interplay between cellular and mechanical processes during biofilm development on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 72 publications
0
58
0
Order By: Relevance
“…Therefore some have suggested that patterning mechanisms do not act alone but that hybrid mechanisms are more likely to be actually found in nature [55]. One example of this is the formation of biofilm structures [56,57]. The mechanism is highly multidimensional and combines many -if not all -of the mechanisms we have presented here for pattern formation.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore some have suggested that patterning mechanisms do not act alone but that hybrid mechanisms are more likely to be actually found in nature [55]. One example of this is the formation of biofilm structures [56,57]. The mechanism is highly multidimensional and combines many -if not all -of the mechanisms we have presented here for pattern formation.…”
Section: Resultsmentioning
confidence: 97%
“…This simple versatile stabilizing strategy is highly expected to other systems for the controlled fabrication of patterned self-supported crack-free films with desirable functions and unprecedented applications. Additionally, the stable wrinkling patterns are obtained through the similar approach in the living systems, in which cell division and differentiation generate and modulate internal stresses to form stabilized hierarchical patterns57, such as fingerprints and the topological conformation of some fruits. Our system might serve as a model system to understand the formation of complex multi-scale micro-textures of biofilms on various substrates, in which the similar stabilizing effect may be involved5859.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm models incorporating additional biological (in particular the role of EPS [18]) and mechanical processes, following similar approaches as explored in e.g. [15,33], may provide a complementary understanding of biofilm pattern formation.…”
Section: Discussionmentioning
confidence: 99%